Ohmic Heating as Alternative Preservation Technique - A Review - Muhammad, A. I.; Shitu, A.; Tadda, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The quest for new technologies in heating has drawn the attention of researchers to focus on energy saving and efficient techniques in heating food materials. Ohmic heating is one of these technologies because it heats both phases of food (liquid and solid) simultaneously by internal energy generated from electrical power. Using this method, the product undergoes minimum structural damage, retains its nutritional value, and is processed within a shorter time than with conventional heating methods. The technique also gives excellent processed quality products with lower energy cost. The heat energy generated during ohmic heating is transferred directly into the foods. The electrical conductivity of food products is linear with different temperature ranges and varies with heating time, food structure, and its constituents. As such, ohmic heating can be applied in different pre-processing and processing operations like drying, evaporation, dehydration, blanching, fermentation, extraction, sterilization, and pasteurization. This paper highlights ohmic heating as an emerging alternative novel heating technology to meet the demand for industrial and domestic food processing. Recommendations were made for further research to provide a more robust analysis of ohmic heating performance.